Consumo, digestibilidade e parâmetros ruminais de cordeiros alimentados com dietas contendo níveis crescentes de triguilho - Piran Filho, Francisco Antonio (2018)
The aim was to evaluate the effect of inclusion of increasing levels of wheat middling on intake, digestibility and ruminal parameters of lambs. Eight 45 ± 9 kg crossbred Santa Inês x Dorper, castrated, shared into two groups, four rumen fistulated and four non - fistulated animals, each organized in a 4x4 Latin square design. The animals were fed ad libitum, with 10% of leftovers, twice a day. The base diet was composed of ryegrass hay and concentrate, in the ratio 40:60 bulky:concentrate. The assay was composed of four treatments: T-0 = control treatment (0% of wheat middling), T-19 = treatment with 19% of wheat middling, T- 38 = treatment with 38% of wheat middling and T-57 = treatment with 57% of wheat middling in the diet. The inclusion of increasing levels of wheat middling in the diet of lambs decreased intake (g day-1) for most nutritional components, however, when expressed in relation to metabolic weight intake was less affected. For rumen fistulated lambs the inclusion of wheat middling did not promote alteration in rumen parameters and nitrogen balance, however, fiber digestibility was reduced even without pH change. As for the group of nonfistulated lambs, the inclusion of wheat middling decreased metabolic fecal excretion and increased total apparent digestibility of nitrogen and ethereal extract. Up to 38% inclusion of wheat middling in the diet of lambs consumption was able to meet the protein requirements, however, the treatment with 57% of wheat middling was not attended and could compromise animal performance, therefore, this level of inclusion is not indicated.